Variations and Hybridization Compatibility of Single Basidiospore Isolates of Pleurotus sajor-caju (Fr.) Sings - Fung, Jessica Lee Ying; Mohamad Hasnul., B; Kuok, Freddy San Yeo (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Pleurotus sajor-caju (Fr.) Sings, a mushroom of the family Pleurotaceae, is gaining popularity due to its high nutrient content and capability of growing on various agricultural wastes. There is a need to breed new strain of P. sajor-caju to meet the rising demands of the increasing human population. Strain improvement is achievable through selection and hybridization. Unfortunately, there is limited information regarding the genetic variations of P. sajor caju in Malaysia. Therefore, this study is of interest to document the morphological variations of single basidiospore isolates and to generate hybrids. A total of 200 single basidiospore isolates (SB) obtained from a commercialized strain of P. sajor-caju were obtained from local supermarket in Kuching, Sarawak, and cultured individually on potato dextrose agar. These 200 SBs were characterized morphologically and divided into three main groups based on colony morphology i.e. scattered, rough and smooth. Variations can still be observed in each main group. From each main group, SBs representing the variations were further categorized based on their colony diameter growth after 7 days of post inoculation (CD-7dpi), i.e. slow growing CD-7dpi (SGCD-7), medium fast growing CD-7dpi (MFGCD-7) and fast growing CD-7dpi (FGCD-7). Ten FGCD-7 and ten SGCD-7 isolates were selected for hybridization. The selected SBs were hybridized in all possible pairings without repetition. Sixteen hybridized isolates were recognized and characterized based on CD-7dpi. For all FGCD-7 pairings, SGCD-7 pairings, and between FGCD-7 and SGCD-7 pairings, hybridized isolates had higher CD-7dpi than at least one of its parents were identified. The new hybridized isolates are interesting materials for future study.